Minding the Gap: Academic Outcomes from Pre-college Programs - Phoebe Kotlikoff; Ahmed S. Rahman; Katherine Smith (Institute of Labor Economics (IZA), 2021)
This paper analyzes the effects of assignment to a one-year college preparatory program on academic performance in college. To measure the value added from pre-college programs, we use a large dataset of United States Naval Academy students from the 1988 to 2018 graduating classes, of which a little over 22% received post-high school remediation. Given the Academy's unique admissions criteria that members of each incoming class originate from an even distribution of congressional districts, we instrument for pre-college treatment using the number and quality of other applicants originating from the same district. After incorporating these instruments as well as a wide range of outcome measures and background characteristics, we find that preparatory programs have positive but limited effects for human capital development for undergraduate students. Specifically, these pre-college programs promote significant but short-lived improvements in academic grades. They also can encourage students to choose STEM-oriented majors, and promote retention by lowering voluntary exits.
Keywords: I20; J24; 330; human capital; remedial education; higher education; liberal arts college